Mastering Kubernetes : level up your container orchestration skills with Kubernetes to build, run, secure, and observe large-scale distributed apps /: level up your container orchestration skills with Kubernetes to build, run, secure, and observe large-scale distributed apps. (2020) - Sayfan, Gigi
No abstract available